Metabolically active angiosperms survive passage through the digestive tract of a large-bodied waterbird. Issue 3 (22nd March 2023) - Paolacci, Simona; Jansen, Marcel A. K.; Stejskal, Vlastimil; Kelly, Thomas C.; Coughlan, Neil E.
Abstract : Avian vectors, such as ducks, swans and geese, are important dispersers of plant propagules. Until recently, it was thought that small vegetative propagules were reliant on adherence to vectors and are unlikely to survive passage through the avian digestive tract. Here, we conclusively demonstrate that metabolically active angiosperms can survive passage through the digestive tract of a large-bodied waterbird. In addition, we show that extended periods of air exposure for up to 7 days does not inhibit the survival of plantlets embedded in faecal matter. Following air exposure, plantlets ( n = 3000) were recovered from 75 faecal samples of mute swans, Cygnus olor, with the survival of 203 plantlets. The number of recovered and surviving plantlets did not significantly differ among durations of air exposure. For recovered plantlets, the long-term viability and clonal reproduction of two duckweed species, Lemna minor and L. gibba, were confirmed following greater than eight months of growth. These data further amplify the key role of waterbirds as vectors for aquatic plant dispersal and demonstrate the internal transport (i.e. endozoochory) of metabolically active plantlets. These data suggest dispersal of vegetative plant propagules by avian vectors is likely to be a common occurrence, underpinning connectivity, range expansion and invasions of some aquatic plants.